Ventilator provision strategy in a large tertiary medical center - Tanchuco, Joven Q. (2017.)
Patients in critical condition are often brought to a tertiary medical center with expectations that they will find relief and improvement of their conditions. Frequently, supportive measures are rendered while waiting for therapeutic interventions to take effect. One such supportive measure is giving ventilatory support to patients who have developed respiratory failure. The hospital should therefore always have sufficient numbers of ventilators that are needed to provide this. As the need for these ventilators is unpredictable, fluctuates widely and must be provided immediately, a hospital needs to balance being able to have enough ventilators all the time while minimizing expensive idle equipment. This study was thereforeundertaken to look into a sustainable strategy to provide sufficient number of ventilators. A combination of quantitative and qualitative methods was used to identify the optimal strategy for ventilator provisioning. For the quantitative part, data on ventilator use were obtained as the number of ventilators per day (ventilator days) over a period of four years (2014-2017). Considering the stature of the hospital under the study and the expectations of its patient market, a target of being able to provide the ventilators neede per day for 90% of any given day in a month was set. From this, it was found that 11 respirators were needed to meet the 90% target. This meant acquiring three more ventilators as the hospital already owned eight. Financial analysis using Monte Carlo simulation was then used to look into four provisioning strategies for the three additional ventilators: three ownership strategies (outright purchase, installment, and staggered purchase) and one rental strategy. Return on Investment (ROI), Internal Rate Return (IRR), Modified Internal Rate of Return (MIRR), Net Present Value (NPV) and Payback (or Breakeven point) were determined using Excel 2016. The installment strategy proved to have the best performance, followed by outright purchase and staggered purchase. The rental proved to be least attractive financially. However, the Rental strategy should be maintained as it can provide the remaining 10% of the ventilator needs. For the qualitative part, questionnaires were given to those involved in providing ventilatory support, namely: doctors, nurses and respiratory therapists. Doctors wanted more sophisticated machines and felt that rental respirators did not provide these. Nurses reported that patients are often affected when the respirators sound an alarm which frequently happens with rental machines. While respiratory therapists state that the rental respirators malfunctioned more frequently than those owned by the hospital. Based on these findings, it is recommended that the hospital acquire three more ventilators as this will provide sufficient machines 90% of the time. The best strategy to do this is by installment but even outright purchase will also be attractive financially. The rental strategy should only be maintained to provide ventilators in the remaining 10% of the time. Anytime a hospital-owned respirator becomes available, it should immediately be utilized after proper cleaning. JOVEN Q. TANCHUCO
Available in CD, pdf copy.
A Study Presented to the Faculty of the Graduate Program in Hospital Administration, College of Public Health, University of the Philippines Manila
Keywords: Hospitals -- Respiratory services; Respirators (Medical equipment).